Escondidos como Anne Frank : 14 historias de supervivencia. - Prins, Marcel; Steenhuis, Peter Henk; Padilla, Ignacio (México : Santillana, 2016)
.
.
Con fotografías de los niños escondidos, hoy en día.
Keywords: .